Time-course evaluation of intestinal structural disorders in a porcine model of intra-abdominal hypertension by mechanical intestinal obstruction. - Ester Párraga Ros; Laura Correa-Martín; Francisco M Sánchez-Margallo; Irma Eugenia Candanosa-Aranda; Manu L N G Malbrain; Robert Wise; Rafael Latorre; Octavio López Albors; Gregorio Castellanos (PLoS ONE, 2018)
A mechanical intestinal obstruction (MIO) can generate intraabdominal hypertension (IAH) that is life threatening. The intestines are very sensitive to IAH since the low splanchnic perfusion causes intestinal hypoxia, local acidosis and bacterial translocations. This may lead to acute intestinal distress syndrome (AIDS). The identification of intestinal injuries during IAH and its correlation with clinical parameters as the abdominal perfusion pressure (APP), the gastric intramucosal pH (pHi) and lactic acid (Lc) are still unknown. This study aimed to evaluate the sequence of intestinal histopathological findings in an MIO model and to analyze potential relationships with parameters currently used in clinical practice (APP, pHi and Lc).Twenty pigs were divided into three groups: a control group (n = 5) and two experimental groups with 20 mmHg (G1, n = 10) and 30 mmHg (G2, n = 5) of IAH by MIO. The pressures were maintained for 3 hours, except in 5 animals in G1 where it was maintained for 5 hours. The APP, pHi and LA were recorded and biopsies of the terminal ileum were taken every 30 minutes in all groups. The intestinal damage was graded according to the Park Score.Intestinal injuries were found in 42.9% of pigs in the experimental groups. The lesions were independent of the level and duration of IAH. Although APP and pHi were slightly lower in injured animals (I +) of G1 and G2, there were no significant differences among those uninjured (I-). Lc was significantly increased in all I+ pigs from the onset of IAH.The IAH by MIO causes intestinal lesions from the first 30 minutes with concurrent decreases in APP and pHi and increases in Lc. Lc could be the best clinical parameter related to intestinal damages with a clear difference between I + and I- animals.